Effectiveness of rehabilitative interventions beginning within the first month of stroke onset in improving lower extremity-related outcomes: a systematic review and network meta-analysis - Yeo Yh; Razali Mf; Ripin Zm; Ridzwan Miz (Penerbit UKM, 2023)
Reviews about early interventions, which are important in stroke rehabilitation due to significant neural plasticity, are relatively less. This study objective was to investigate the effectiveness of different interventions started within one-month post-stroke in improving lower extremity-related outcomes as compared to conventional rehabilitation and the corresponding effectiveness ranking. Cochrane Library, Ovid, PubMed, and Scopus were searched for articles dated up to 18 March 2022. Randomised controlled trials were included if they evaluated the effectiveness of two or more different non-drug, non-invasive, and non-surgical interventions which were started within one-month post-stroke on lower extremity-related outcomes. Network meta-analysis revealed that transcranial direct current stimulation, repetitive transcranial magnetic stimulation, mirror therapy, cycling, transcutaneous auricular vagus nerve stimulation, neuromuscular electrical stimulation (NMES), combination of robot and NMES, and thermal stimulation were significantly more effective in improving lower extremity motor function than conventional rehabilitation. In improving mobility, mirror therapy, cycling, and thermal stimulation were significantly more effective. In enhancing balance, physio ball, transcutaneous electrical nerve stimulation, cycling, thermal stimulation, and robot showed significantly higher effectiveness. Thermal stimulation scored the highest effectiveness ranking in improving lower extremity motor function and mobility whereas robot and backward walking achieved the highest effectiveness ranking in improving balance and gait speed respectively.